Assessment of volatile compounds, neutral and polar lipid fatty acids of four beef muscles from USDA Choice and Select graded carcasses and their relationships with consumer palatability scores and intramuscular fat content. (June 2016) - Hunt, M.R.; Legako, J.F.; Dinh, T.T.N.; Garmyn, A.J.; O'Quinn, T.G.; Corbin, C.H.; Rathmann, R.J.; Brooks, J.C.; Miller, M.F.
Abstract: Fatty acids (FA) in neutral and polar lipids (NL and PL) and volatile compounds were determined in Gluteus medius (GM), Longissimus lumborum (LL), Serratus ventralis (SV), and Semimembranosus (SM) muscles from upper 2/3 USDA Choice and Select quality grades (QG). Concentrations of NL FA (mg/g) were influenced by intramuscular fat (IMF) content being greater in upper 2/3 Choice compared with Select. The SV contained greater concentrations of NL FA; meanwhile, the SM contained the lowest quantities of NL FA. Percentages (g/100 g of total FA) of NL SFA and MUFA were increased in beef with greater IMF content. Concentrations and percentages of PL FA had muscle specific differences between QG. Volatile compounds were primarily affected by muscle. Increases in SFA and MUFA were related with consumer liking, regardless of lipid fraction. Overall the influence of QG on SFA and MUFA was muscle specific. Therefore, each muscle may require specific considerations when considering FA, volatile compounds, and ultimately consumer liking. Highlights: Chemical components of beef muscles and USDA quality grades were measured. Muscle greatly impacted volatile compound concentrations. Intramuscular fat content affected neutral and polar lipid fatty acids. Some polar lipid fatty acids were influenced by quality grade dependent on muscle. Neutral and polar lipid fatty acids were correlated with flavor liking.